Contemporary incidence of stroke (focal infarct and/or haemorrhage) determined by neuroimaging and neurodevelopmental disability at 12 months of age in neonates undergoing cardiac surgery utilizing cardiopulmonary bypass. (8th December 2017) - Verrall, Charlotte E; Walker, Karen; Loughran-Fowlds, Alison; Prelog, Kristina; Goetti, Robert; Troedson, Christopher; Ayer, Julian; Egan, Jonathan; Halliday, Robert; Orr, Yishay; Sholler, Gary F; Badawi, Nadia; et al.
Abstract: OBJECTIVES: When evaluated prospectively, acute brain injury is reported in up to 75% of neonates undergoing cardiopulmonary bypass (CPB), predominantly white matter injury rather than stroke. This study investigates the incidence of stroke (focal infarct and/or haemorrhage) detected by neuroimaging in contemporary clinical practice, whereby magnetic resonance imaging/computed tomography routinely occurs in response to clinical events, comparing those undergoing the Norwood procedure with those undergoing other neonatal procedures involving CPB, and defines the relationship between stroke and neurodevelopmental disability (NDD) at 12 months of age. METHODS: One hundred and twenty neonates underwent CPB between July 2011 and December 2014: 25 Norwood procedures and 95 non-Norwood procedures. Data were retrospectively collected including clinical data and 12-month neurodevelopmental assessment using the Bayley Scales of Infant and Toddler Development, Third Edition (BSID-III). RESULTS: Stroke was detected in 12% of neonates in current clinical practice: 24% of the Norwood group vs 8% of the non-Norwood group ( P  = 0.03). Significant predictors of stroke in the univariate analysis included the Norwood procedure, lowest operative temperature and use of extracorporeal membrane oxygenation ( P  < 0.05). The lowest operative temperature and use of extracorporeal membrane oxygenation remained significant in the multivariate analysis ( P  < 0.05). Fifty-seven percent were assessed using the BSID-III assessment, and 68% demonstrated NDD in at least 1 subscale. In neonates who suffered stroke, the incidence of NDD was significantly greater in 4/5 subscales compared with those with no injury ( P  < 0.05). The Norwood group had a significantly greater incidence of NDD in 2/5 subscales when compared with the non-Norwood group ( P  < 0.05). CONCLUSIONS: Stroke, established by neuroimaging in contemporary clinical practice, was detected in 12% of neonates having CPB, and those undergoing the Norwood procedure have a 3-fold risk of injury. Stroke was associated with NDD at 12 months of age.